2007
DOI: 10.4319/lo.2007.52.5.1898
|View full text |Cite
|
Sign up to set email alerts
|

Bioturbation and bioirrigation extend the open exchange regions in permeable sediments

Abstract: Large-scale experimental exclusion of lugworms (Arenicola marina) from 400 m 2 intertidal fine sand revealed significant effects of their bioturbation and bioirrigation on sediment characteristics, benthic infauna composition, and the dominant mineralization and benthic-pelagic exchange processes in the sediment. Absence of lugworms resulted in sediment clogging with organic-rich fine particles, an eightfold decrease in sediment permeability, low oxygen penetration depths, and accumulation of reduced mineraliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(66 citation statements)
references
References 47 publications
7
55
0
4
Order By: Relevance
“…In support of this, Bertics and Ziebis (2009) found that as the combined bioturbation activities of thalassinidean shrimp and fiddler crabs increased, so did the in situ microbial abundances and oxidationreduction potential. Such effects have also been observed in sediments inhabited by lugworms, which resulted in changes in the pore-water chemistry of the entire permeable sediment (Volkenborn et al, 2007). Nevertheless, recent investigations have noted the differences between sediment characteristics in situ and mesocosm sediments (Papaspyrou et al, 2007), and it would be beneficial to confirm the conclusions of this study by comparison with in situ exclusion studies.…”
Section: Figuresupporting
confidence: 71%
“…In support of this, Bertics and Ziebis (2009) found that as the combined bioturbation activities of thalassinidean shrimp and fiddler crabs increased, so did the in situ microbial abundances and oxidationreduction potential. Such effects have also been observed in sediments inhabited by lugworms, which resulted in changes in the pore-water chemistry of the entire permeable sediment (Volkenborn et al, 2007). Nevertheless, recent investigations have noted the differences between sediment characteristics in situ and mesocosm sediments (Papaspyrou et al, 2007), and it would be beneficial to confirm the conclusions of this study by comparison with in situ exclusion studies.…”
Section: Figuresupporting
confidence: 71%
“…Thus, engineering by these species potentially ampliWed the eVects of lugworm absence. In 2004, sediment permeability on experimental exclusion plots in the low intertidal had fallen below the critical value where lugworms can thrive (Volkenborn et al 2007b). The contrasting eVects of both functional types of benthic bio-engineers suggest that mutual exclusion may not only be a product of localised disturbance or sediment binding, but involve long-lasting, sediment-mediated processes.…”
Section: Mobility-mode Hypothesis and Benthic Bio-engineeringmentioning
confidence: 99%
“…These include solute transport processes (e.g., Jørgensen and Revsbech, 1985;Huettel and Gust, 1992;Janssen et al, 2005;Bühring et al, 2006), temperature (e.g., Pamatmat and Banse, 1969;Banta et al, 1995;Thamdrup et al, 1998), hydrodynamic forces (e.g., Jørgensen and Des Marais, 1990;Søndergaard et al, 1992;Almroth et al, 2009;Holmroos et al, 2009), macrofauna and microbial community (e.g., Jørgensen, 1977;Volkenborn et al, 2007;Na et al, 2008), organic matter sources (e.g., Banta et al, 1995;Conley and Johnstone, 1995;Stephens et al, 1997) and oxygen saturation in the overlying water column (e.g., Rasmussen and Jørgensen, 1992) and its penetration into the sediment (e.g., Huettel and Gust, 1992;Cardenas et al, 2008).…”
Section: Introductionmentioning
confidence: 99%